The Implementation of Integration of Religion and Science at State Islamic Higher Education - Imam Subchi (Jurnal Penelitian, 2020)
This research investigated the integration of religion and science in the state of Islamic higher education. Methods of the investigation were library research of published and unpublished documents on the process and implementation of integration of science and religion at three state Islamic universities: the State Islamic University Syarif Hidayatullah Jakarta, the State Islamic University Sunan Kalijaga Yogyakarta, and the State Islamic University of Maulana Malik Ibrahim Malang. Data obtained using the following databases: Google Scholar, Sinta- Science and Technology Index, Ebsco-host, Study gate, Sage Journal, Free Scientific Electronic Library (SciELO), and others. The findings showed that there is poor integration of religion and science within the three universities. This conclusion can be seen from the analysis of the students' final report, theses and dissertations from these three universities. This study suggests a further assessment of all State Islamic Universities by the Ministry of Religious Affairs in promoting the integration of religion and science in State Islamic Higher Education.